2004
DOI: 10.1016/j.ehj.2004.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Low physical activity as a predictor for total and cardiovascular disease mortality in middle-aged men and women in Finland

Abstract: Moderate and high levels of leisure time and occupational physical activity are associated with a reduced CVD and all-cause mortality among both sexes. Promoting already moderate levels of leisure time and occupational physical activity are essential to prevent premature CVD and all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
188
5
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(212 citation statements)
references
References 43 publications
12
188
5
7
Order By: Relevance
“…Analyses of the association between work-related physical activity and mortality provided conflicting results. They range from a protective effect (Autenrieth et al, 2011;Barengo et al, 2004;Samitz et al, 2011) to no effects (Besson et al, 2008) (in line with our results) to deleterious effects, at least in men (Herzig et al, 2012). Null findings between occupational physical activity and mortality may be due to residual confounding or the broad physical activity categorisation due to job type only.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Analyses of the association between work-related physical activity and mortality provided conflicting results. They range from a protective effect (Autenrieth et al, 2011;Barengo et al, 2004;Samitz et al, 2011) to no effects (Besson et al, 2008) (in line with our results) to deleterious effects, at least in men (Herzig et al, 2012). Null findings between occupational physical activity and mortality may be due to residual confounding or the broad physical activity categorisation due to job type only.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to others (Andersen et al, 2000;Autenrieth et al, 2011;Barengo et al, 2004;Samitz et al, 2011), there were no effects of work-related and commuting activities on mortality. The promotion of physical activity offers large potential for health improvement and mortality reduction in the population.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…While some inverse associations have been reported between occupational activity and obesity and its associated sequelae (King et al, 2001;Barengo et al, 2004;Mummery et al, 2005), others have found no association (Ball et al, 2001;GutierrezFisac et al, 2002). The majority of this work investigates Model 2 also includes occupational activity as specified in Model 1, results did not substantially differ so are not shown above.…”
Section: Discussionmentioning
confidence: 98%